Opportunities from Open Source Search - Buntine, Wray; Aberer, Karl; Podnar, Ivana; Rajman, Martin (IEEE/WIC/ACM International Conference on web intelligence, 2005)
Internet search has a strong business model that permits a free service to users, so it is difficult to see why, if at all, there should be open source offerings as well. This paper first discusses open source search, and a rationale for the computer science community at large to get involved. Because there is no shortage of core open source components for at least some of the tasks involved, the Alvis Consortium is building infrastructure for open source search engines using peer-to-peer and subject specific technology as its core, based on this rationale. We view open source search as a rich future playground in which information extraction and retrieval components can be used and intelligent agents can operate.